Acquired brain injury : an integrative neuro-rehabilitation approach - Aquino, Nicole; Chang, Johanna L.; Drucker, Jennifer; Duarte, Robert A.; Elbaum, Jean 1960- (Switzerland Springer, 2019)
This book presents a comprehensive interdisciplinary team approach to the rehabilitation of acquired brain injury (ABI) survivors. Medical and clinical specialists will receive a deeper understanding of not only each other's roles but of their complementary functions in this field. Many case examples are provided, illustrating a wide range of challenges and stages of recovery. This edition features 3 entirely new chapters and multiple updated chapters by new and returning authors.
La función de los autores fue determinada por el catalogador
Keywords: DISFUNCION CEREBRAL -- PACIENTES -- REHABILITACION; CEREBRO -- HERIDAS, LESIONES, ETC